Short-term glucocorticoid intake combined with intense training on performance and hormonal responses - Collomp, K.; Arlettaz, A.; Portier, H.; Lecoq, A. M.; le Panse, B.; Rieth, N.; de Ceaurriz, J. (British Journal of Sports Medicine, 2008)
Objective: To investigate the effects of short-term prednisolone ingestion combined with intense training on exercise performance, hormonal (adrenocorticotrophic hormone (ACTH), prolactin, luteinising hormone (LH), growth hormone (GH), thyroid-stimulating hormone (TSH), dehydroepiandrosterone (DHEA), testosterone, insulin) and metabolic parameters (blood glucose, lactate, bicarbonate, pH).